Emergency Airway Management of Neonatal Cystic Hygroma: A Systematic Review and Meta-Analysis. - Agarwal, Shilpa; Agarwal, Neeti; Soni, Vikas; Agarwal, P. D. (Journal of Neonatal Surgery, 2024)
Background: Cystic hygroma is a benign congenital lymphatic malformation predominantly occurring in the cervicofacial region, frequently presenting life-threatening airway emergencies in neonates and infants. Emergency Airway Management of Neonatal, strategy advocates simplified, minimally invasive interventions over complex procedures in emergency settings. Objective: This study aimed to evaluate the efficacy and safety of the KISS strategy, specifically needle aspiration and simplified airway management techniques, in the emergency management of neonatal cystic hygroma with respiratory distress, through a systematic review and meta-analysis of published literature. Methods: A comprehensive literature search was conducted across PubMed, Scopus, Google Scholar, and Cochrane Library databases for studies published between 2000 and 2025. A total of 18 studies comprising 142 patients were included. Results: The pooled success rate for simplified interventions was 82.4% (95% CI: 75.8–87.9%). Needle aspiration achieved a success rate of 85.7%. The KISS approach significantly reduced the need for emergency tracheostomy (17.6% vs. 42.3%, p < 0.001) and was associated with fewer complications. The in-hospital mortality rate was 4.9%. Conclusion: The KISS strategy represents an effective, safe, and reproducible approach for managing life-threatening airway emergencies in neonatal cystic hygroma, particularly in resource-limited settings.